Trends in the Utilization and Impact of Radiofrequency Ablation for Hepatocellular Carcinoma - Massarweh, Nader N (2010)
BACKGROUND: The incidence of hepatocellular carcinoma (HCC) is rising and radiofrequency ablation (RFA) appears to be increasingly used. The nationwide use and impact of RFA have not been well characterized. STUDY DESIGN: Historical cohort study of US patients ≥18 years with a diagnosis of HCC (n=22,103) using the national Surveillance, Epidemiology, and End Results (SEER) limited-use database (1998-2005). Main outcome measures were receipt of different therapeutic interventions (ablation, RFA, resection, or transplantation) and adjusted one- and two- year survival. RESULTS: 4,924 (22%) patients underwent any intervention with a 93% increase over the eight year study period (trend test, p<0.001). RFA accounted for 43% of this increase. Despite increased use of therapeutic interventions, one- and two-year survival did not improve over time for patients in the study cohort (48% and 34%, 52% and 37%, 50% and 36%; in 1998, 2002, and 2004, respectively; p=0.31). Among patients with solitary lesions, adjusted one- and two-year survival remained stable over time after transplantation (97% and 94%, 95% and 89%, 94% and 86%; p=0.99) and RFA (86% and 64%, 76% and 54%; p=0.97) but improved after resection (83% and 71%, 91% and 84%, 97% and 94%; p=0.03). CONCLUSIONS: Utilization of interventions for the treatment of HCC, and specifically RFA, have markedly increased over time. Since increased use of RFA among potentially resectable patients is likely to occur and because of a lack of high-level evidence supporting expanded indications, continued evaluation of the indications for RFA as well as subsequent outcomes among US patients is warranted.